THE CULTURAL AND HERITAGE TOURISM OBJECTS IN PALEMBANG - Welly Ardiansyah; Iskandar Rosyidin (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2013)
This paper presents a study on potentialities of old buildings in seven historical areas of Palembang; Fort Kuto Besak, Ampera Bridge, Grand Mosque, Sultan Mahmud Badaruddin II Museum, Mayors Office Building, and Kampung Kapitan, that can be explored deeper to be cultural and heritage tourism. To conduct this study, research area was used and to collect the data and information, publications, reports, and observation were the main tools to collect the data. The results indicate that  the old buildings of cultural and heritage tourism in Palembang are reflections of the multi-ethnic societies of the era such as Dutch, Arab, Indian, and Palembang Darussalam Sultanate, and dominantly they lie  at riverside of Musi river as being the earliest settlements. It also shows that people from other ethnicities can live in harmony and tolerance.